Effect of ethylene carbonate addition on ion aggregates, ion pairs and free ions of polyvinyl alcohol-methylcellulose host: Selection of polymer electrolyte for possible energy devices application - Rojudi, Z.E. (Springer Science and Business Media B.V., 2022)
The enhancement of electrical and structural properties of polyvinyl alcohol (PVA)-methylcellulose (MC)- ammonium thiocyanate (NH4SCN) system with ethylene carbonate (EC) has been conducted using solution cast method. The percentage of ion aggregates, ion pairs and free ions in the electrolyte is revealed via Fourier transform infrared spectroscopy (FTIR). This information is crucial for energy storage applications. The polymer-salt-plasticizer interactions have been verified as there are changes in the position of the peak as EC is added. The addition of EC has enhanced the ionic number density but as more than 20 wt. EC is added, a drop in ion mobility and diffusion was observed. It can be confirmed via X-ray diffraction (XRD) analysis that the crystallite size and crystallinity of PVA-MC have reduced with addition of 20 wt. EC. The surface morphology of the highest conducting sample was found to have a porous structure. From constant phase element (CPE), 20 wt. possesses the high capacitance of 5.35 Ã 10â5 F. An optimum conductivity of 1.59 Â± 1.25 Ã 10â3 S cmâ1 was attained at a composition of 20 wt. EC. Therefore, the developed PVA-MC-NH4SCN-EC electrolyte showed an excellent potential as an electrolyte material in any energy devices application due to its good performance in ionic conductivity, highly amorphous and mechanically stable. Â© 2022, The Polymer Society, Taipei.